2017
DOI: 10.5398/medpet.2017.40.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Red Dragon Fruit (Hylocereus polyrhizus) Peel Extract as the Colorant, Antioxidant, and Antimicrobial on Beef Sausage

Abstract: This study aimed to evaluate the effectiveness of red dragon fruit (Hylocereus polyrhizus) peel extracts addition on beef sausages. Red dragon fruit peel extracts were obtained by maceration using solvent at pH 5. Phytochemical characteristics, total phenols, antioxidant, and antimicrobial activity of the peel extracts were observed. Antioxidant and antimicrobial activities of the extracts were associated with high phytochemical compounds and total phenols contained in the extracts. Red dragon fruit peel extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 17 publications
(24 reference statements)
6
36
0
12
Order By: Relevance
“…For example, H. polyrhizus peel extract added to the product increased antioxidant activity from 49.71% (control sample) to 54.76%, 60.89% and 72.94%, respectively, with 20%, 30% and 40% of the extract. Similar results were obtained for the TBARS parameter [ 75 ]. Another study reported the use of extracts of pomegranate peels and pistachio green hulls to decrease the formation of MDA [ 74 ].…”
Section: Beneficial Effects Of Plant Extracts In Meat Productssupporting
confidence: 87%
See 2 more Smart Citations
“…For example, H. polyrhizus peel extract added to the product increased antioxidant activity from 49.71% (control sample) to 54.76%, 60.89% and 72.94%, respectively, with 20%, 30% and 40% of the extract. Similar results were obtained for the TBARS parameter [ 75 ]. Another study reported the use of extracts of pomegranate peels and pistachio green hulls to decrease the formation of MDA [ 74 ].…”
Section: Beneficial Effects Of Plant Extracts In Meat Productssupporting
confidence: 87%
“…This approach could also be applied to plant wastes (e.g., fruit peel). Manihuruka et al [ 75 ] suggested the use of red dragon fruit ( Hylocereus polyrhizus ) peel as a natural colorant and antioxidant. Although the peel contains betacyanins, the redness of beef sausage was found to be less intense, which could be due to the degradation of betacyanins after the boiling process (60–65 °C, 60 min.).…”
Section: Beneficial Effects Of Plant Extracts In Meat Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ekstrak kulit buah naga merah memiliki kandungan antioksidan berupa vitamin C, flavonoid, tanin, alkaloid, steroid, dan saponin berdasaran hasil pengujian fotokimia dan FTIR (Noor, 2016). Buah naga mengandung berbagai senyawa aktif diantaranya tiamin, niasin, piridoksin, kobalamin, fenolik, betacyanin, polifenol, karoten, likopen, kaempferol, betacyanin, quercetin dan isorhamnetin dalam melawan radikal bebas (Manihuruk et al, 2017).…”
Section: Hasil Penelitian Dan Pembahasan Potensi Antioksidan Pemunclassified
“…The thiobarbituric acid reactive substances (TBARS) was evaluated according to Manihuruk et al (2017)…”
Section: Tbars Analysismentioning
confidence: 99%